A constituição histórica do Gymnasio São Vicente De Paulo (1913- 1931) - Lyrio, Patrícia Seibert (2023)
This work aims to understand the processes of historical constitution of a private educational institution in the capital of Espírito Santo, Vitória. Gymnasio São Vicente de Paulo (GSVP) was founded by brothers Aristóbulo Barbosa Leão (director), Kosciuszko Barbosa Leão (deputy director) and Miguel Barbosa Leão (secretary). The study focuses on the organization of this high school in a period of 28 years – from the year of its foundation, 1913, to 1931 – starting from the following questions: What was the founding process of the Gymnasio São Vicente de Paulo? Who were the subjects involved in this process? How was the school organized in terms of space, knowledge, and practices? What was the place of Gymnasio São Vicente de Paulo in the educational scene of Espírito Santo in the First Republic? The sources used are documents from the GSVP's school archives, photographs, furniture, government communications, minutes, school journals and newspapers from the period, and the building that housed the school. The analysis is based on Italian microhistory according to Carlo Ginzburg (2007) and Giovanni Levi (2020) and focuses on the method of evidence proposed by Bloch (2009), taking into account the relationships between past and present. In the first decades, the Gymnasium maintained an education based on morality, civics, and Catholic religiosity. The process of founding the Gymnasio São Vicente de Paulo took place at a time when there was a general lack of educational institutions, and aimed especially at secondary education, in dialog with the process of expansion and modernization of the capital of Espírito Santo, considering the expansion of political and social movements. It is also noteworthy that the institution, as a private school, received government incentives in the form of grants and that the educational process was not inclusive of all, but became exclusionary and elitist.